PENGARUH PROFITABILITAS DAN OPINI AUDIT TERHADAP AUDIT DELAY PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Meta Mulidia; Edi Sutanto; Muhammad Wahid Murniawan (Universitas La Tansa Mashiro, 2024)
Audit delay is the length of time for the completion of the audit which is measured from the closing date of the financial year to the date of completion of the independent audit report. This study aims to examine the effect of profitability (return on assets) and audit opinion on LQ45 companies listed on the Indonesia Stock Exchange in 2017- 2021. This research method uses quantitative methods. The sample used in this study were all LQ45 companies listed on the Indonesia Stock Exchange in 2017-2021, totaling 23 companies with 115 observation data. The sampling technique used is purposive sampling. The method used is logistic regression analysis using SPSS 25 software. The results of this study indicate that profitability (return on assets) has a significant effect on audit delay, audit opinion has no significant effect on audit delay.